The inhibiting effect of alpha-based TARE on embolized vessels and neovascularization - Tong, Qianqian; Li, Rou; Wang, Ruizhi; Zuo, Changjing; Li, Danni; Jia, Guorong; Peng, Ye; Li, Xiaohong; Yang, Jian; Xue, Shuai; Bai, Qingyun; Li, Xiao (Frontiers in Bioengineering and Biotechnology, 2022)
Transarterial embolization (TAE) is a personalized technology with precise delivery of chemotherapeutic drug or selective internal radiation therapy for hepatocellular carcinoma (HCC). Beta-emitting radionuclides embolisms for TAE (β-based TARE) are commonly in clinic use via inducing biochemical lethality on tumor cells, while alpha-emitting radionuclides-based embolisms for TAE (α-based TARE) are still under study. Feeding artery plays a key role in tumor growth, metastasis and recurrence. In this research, the auricular central arteries (ACA) of rabbits were embolized with silk fibroin-based microspheres (SFMs) integrated with no nuclides, α (Ra-223) or β (I-131) radionuclides to investigate the influence on vessels. The dynamic TARE-induced tissue apoptosis and the following neovascularization were measured by pathological analysis and 68Ga-DOTA-RGD PET/CT. In results, the microspheres in ACA were up to 60.21% embolized dosage (ED) after the initial distribution, and 21.40% ED remained at 48 h post-embolization. Different with β-based TARE that mainly led to extensive necrosis of surrounding tissues, α-based TARE induced irreversible necrosis of a smaller area surrounded the embolized vessels, that was resulted from the alpha-based destroy on vascular walls and adjacent cells. In RGD PET, the inhibition on neovascularization was fully exhibited in α-based TARE (SUVmax = 0.053 ± 0.004) when compared with control group (SUVmax = 0.099 ± 0.036), normal embolization (SUVmax = 0.240 ± 0.040) and β-based TARE (SUVmax = 0.141 ± 0.026), owing to the avoidance of the embolism-induced detrimental neovascularization. In conclusion, α-based TARE provided a promising strategy for HCC treatments via destroying the embolized vessels and inhibiting neovascularization.